Exercise-induced hypoalgesia after acute and regular exercise: experimental and clinical manifestations and possible mechanisms in individuals with and without pain - Henrik Bjarke Vaegter; Matthew David Jones (PAIN Reports, 2020)
Abstract. Exercise and physical activity is recommended treatment for a wide range of chronic pain conditions. In addition to several well-documented effects on physical and mental health, 8 to 12 weeks of exercise therapy can induce clinically relevant reductions in pain. However, exercise can also induce hypoalgesia after as little as 1 session, which is commonly referred to as exercise-induced hypoalgesia (EIH). In this review, we give a brief introduction to the methodology used in the assessment of EIH in humans followed by an overview of the findings from previous experimental studies investigating the pain response after acute and regular exercise in pain-free individuals and in individuals with different chronic pain conditions. Finally, we discuss potential mechanisms underlying the change in pain after exercise in pain-free individuals and in individuals with different chronic pain conditions, and how this may have implications for clinical exercise prescription as well as for future studies on EIH.